2008
DOI: 10.1177/0192513x07311951
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Daughter Communication About Sex and Sexual Intercourse Among Middle- to Upper-Class African American Girls

Abstract: This study investigated linkages between various dimensions of mother— daughter communication about sex and sexual intercourse in a sample of 274 middle- to upper-income African American adolescent girls, drawn from the National Longitudinal Study of Adolescent Health. Logistic regression analysis revealed that girls who reported closer relationships with their mothers were less likely to have had sexual intercourse. They were more likely to report a history of sexual intercourse when their mothers communicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
0
34
0
2
Order By: Relevance
“…Similar to a study by Usher-Seriki, Bynum, & Callands (2008), the content of messages conveyed by the mothers in this study involved negative consequences of unprotected sex, sexually transmitted diseases and birth control. Usher-Seriki et al (2008) found that more frequent communication about these general sexual topics predicted an increased likelihood that adolescents were sexually active, and conversations specific to sexual values (e.g., negative impact of teen pregnancy), were linked to a decreased likelihood of sexual activity.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar to a study by Usher-Seriki, Bynum, & Callands (2008), the content of messages conveyed by the mothers in this study involved negative consequences of unprotected sex, sexually transmitted diseases and birth control. Usher-Seriki et al (2008) found that more frequent communication about these general sexual topics predicted an increased likelihood that adolescents were sexually active, and conversations specific to sexual values (e.g., negative impact of teen pregnancy), were linked to a decreased likelihood of sexual activity.…”
Section: Discussionmentioning
confidence: 77%
“…Usher-Seriki et al (2008) found that more frequent communication about these general sexual topics predicted an increased likelihood that adolescents were sexually active, and conversations specific to sexual values (e.g., negative impact of teen pregnancy), were linked to a decreased likelihood of sexual activity. Both types of messages were conveyed in the present study, although sexual values emerged as a topic of empowering and respecting oneself, and making informed, proactive and positive choices.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is also possible that unmeasured aspects of extended family sexuality communication, such as its content or process, are more permissive than communication with parents. For example, while parental messages discouraging sexual activity have been associated with teens’ delaying sex (Trejos-Castillo & Vazsonyi, 2009; Usher-Seriki, Bynum, & Callands, 2008), messages from extended family members may be different, and less tied to healthy teen behaviors. However, findings for associations between extended family support and reduced risky sexual behavior (Ahrens et al, 2008; Hurd & Zimmerman, 2010) suggest that extended family members may serve as a health-promoting influence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior findings that parent-teen sexuality communication can protect teens from risky sexual behavior (Murry et al 2014; Usher-Seriki et al 2008) suggest that talking with other family members about sex may have a protective influence. This may be particularly true for teens of early parents, where a broader family ecology, rather than solely parental relationships, may provide a base of family support.…”
Section: Discussionmentioning
confidence: 99%